Orchard locality and postharvest oxalic acid application influence fruit quality and shelf life of Jamun (Syzygium cumini L.) fruit - Aslam, Muhammad Majid; Sami Ullah; Razzaq, Kashif; Rajwana, Ishtiaq Ahmad; Akhtar, Gulzar; Faried, Hafiz Nazar; Amin, Muhammad; Unsar Naeem Ullah; Khalil, Uzman (Journal of Pure and Applied Agriculture, 2023)
Jamun is a highly nutritious fruit crop having a short shelf life. This study was performed to evaluate the effect of harvest location and oxalic acid treatment on fruit quality, shelf life, biochemical attributes and antioxidative activity in jamun fruit under ambient conditions. The fruit was sourced from two different locations in the Multan region and subjected to various postharvest oxalic acid (OA) applications (T0: Control, T1: 0.5 mM, T2: 1 mM, T3: 2 mM). The treated fruits were subjected to physicochemical evaluation at shelf under ambient environment (25±2 ºC & 55-60% RH). Harvest location significantly affected various physical, biochemical and antioxidative attributes of jamun fruit. The fruit harvested from OrchardII exhibited lower weight loss and fruit shriveling with higher titratable acidity (TA), vitamin C, total phenolic contents (TPC) and enzyme activity of superoxide dismutase (SOD), while, soluble solid contents (SSC), SSC: TA ratio, total antioxidants and activities of catalase